Reduzir a dose de radiação em crianças que realizaram tomografia computadorizada de crânio não traz prejuízo ao diagnóstico, motiva a educação permanente e promove campanha de radioproteção - Bernardo, Mônica Oliveira (2013)
Radiological examinations have greatly increased, especially in children after craniocerebral trauma (CCT). Recent studies indicate a higher incidence of cancer and cataracts in children undergoing computed tomography (CT) compared to those without exposure. Some countries have promoted campaigns to avoid unnecessary CT and reducing the radiation dose. Objectives: 1. To assess whether the reduction of radiation dose in CT affect exam interpretation and diagnosis in children with CCT. 2. To stimulate discussion and implementation of measures to reduce the radiation dose received by children requiring health care and, also, stimulating awareness of pediatricians and families about the radiation dangers. Methods: We selected two groups of CT from children with CCT that underwent to CT performed in Philips 64 channels Multi Slice CT scanner at Unimed Hospital (Sorocaba-SP) from January to August 2012. We initially selected the 30 last CT performed with usual radiation dose in children. Then to the next CT for CCT we apply the protocols to reduce radiation load (approximately 50%) according to the guidelines of The Alliance for Radiation Safety in Pediatric Imaging. We reduced the kilovoltage (KV) to the maximum shown by tomography equipment and set a limit to the milliamperes per second (mAs) according to analysis of the tomography equipment after the completion of digitized radiography tomography, according to thickness and length of area of the patient being examined. We oriented the technical team to restrict the exam to the extent of the area requested by the doctor. The two CT series were presented to 19 pediatricians and 02 neurosurgeons from the Emergency Unit and to 7 radiologists from Unimed Hospital blind to the technical differences. The participants answered a specific questionnaire asking if they noticed any difference comparing the two series of exams; if they had any difficulty in making the diagnosis and taking the necessary conduct; if they need any training to exam the CTs and to assess the load of radiation and, finally, if they consider useful to implement a booklet for each child to register his/her radiological examinations. Results: Four participants noticed differences between the CT series and reported greater "noise" (image graininess) in those with reduced radiation load, had no difficulty in making a diagnosis and take the right conduct; most would like to have training and education on radioprotection and all agreed that the booklet to register and control radiological examinations would be useful for education and surveillance of parents and health professionals. Conclusion: This study showed that is possible to reduce the radiation dose in CT scans of children up to 50% without loss in the diagnosis accuracy; health professionals are motivated for continuing education and have attitudes to reduce the load of radiation. The direction of the hospital implemented the booklet to record radiological examinations. The campaign was publicized in the local media and on websites of Unimed Sorocaba and Unimed Brazil and has been well accepted by the hospital community and families